Low temperature magnetic structure of CeRhIn5 by neutron diffraction on absorption-optimized samples. (28th March 2017) - Fobes, D M; Bauer, E D; Thompson, J D; Sazonov, A; Hutanu, V; Zhang, S; Ronning, F; Janoschek, M
Abstract: Two aspects of the ambient pressure magnetic structure of heavy fermion material CeRhIn5 have remained under some debate since its discovery: whether the structure is indeed an incommensurate helix or a spin density wave, and what is the precise magnitude of the ordered magnetic moment. By using a single crystal sample optimized for hot neutrons to minimize neutron absorption by Rh and In, here we report an ordered moment of m = 0.54 ( 2 )   μ B . In addition, by using spherical neutron polarimetry measurements on a similar single crystal sample, we have confirmed the helical nature of the magnetic structure, and identified a single chiral domain.